New records of two species of brachyuran crabs (Decapoda: Brachyura) from tropical coastal lagoons, Pacific coast of Mexico - Henickx, Michel E. (1992)
During exploratory sampling in te Altata Ensenada del Pabellon system (24030' N - 107050' W), one of the largest coastal lagoons of western Mexico, located approximately 50 km southwest of Culiacan, Sinaloa, several samples of species of decapod crustaceans were obtained. To of these were immediately recognized as new distribution records for the a Carapace width (c.w.) of collected specimens is provided.